PTH-058 Golimumab: early experience and medium-term outcomes from two uk tertiary ibd centres. (17th June 2017) - Samaan, MA; Pavlidis, P; Akintimehi, AO; Medcalf, L; Chung-Faye, G; Dubois, P; Koumoutsos, I; Anderson, S; Sanderson, J; Hayee, BH; Irving, PM
Abstract : Introduction: Golimumab was granted NICE approval for use in moderate-to-severe ulcerative colitis (UC) in February 2015, based on efficacy demonstrated in the PURSUIT trial program. However, there is relatively little observational effectiveness data regarding its use in clinical practice. We aimed to generate this type of 'real world' data by combining our cohorts at Guy's and St Thomas' and King's College Hospitals. Method: Records of patients commencing golimumab between September 2014 and December 2016 were screened. Those completing at least the 6 week induction phase were included. Clinical activity was evaluated using the Simple Clinical Colitis Activity Index (SCCAI) prior to treatment initiation and at the first clinical review following completion of induction therapy. Response was defined as an SCCAI reduction by 3 points or more. Remission was defined as an SCCAI of less than 3. Continuous data are summarised as medians (range). Pre- and post-induction values were compared using Wilcoxon signed-rank test. Results: 50 UC patients completed golimumab induction therapy (age: 35 (20-72), disease duration 8 years (1-52), prior anti-TNF exposure: 14 (28%), concomitant immunomodulator: 37 (74%), follow-up: 7 months (2-25)). Paired pre- and post-induction SCCAI values were available for 26 patients and fell significantly from 7 (2-19) to 3 (0–8), respectively (p<0.001). Including 8 patients who did not have paired SCCAI data but stopped treatment due to non-response, 18/34 (53%) responded and 10/34 (29%) achieved remission, all of whom were steroid free. The overall rate of corticosteroid usage at golimumab initiation was 24/50 (48%) and withdrawal was successful in 15/24 (63%). Faecal calprotectin fell significantly (pre-induction:1096 (15–4800), post-induction:114 (11–4800), p=0.011 for n=20). CRP fell significantly (pre-induction:4 (1–46), post-induction:2 (1–34), p=0.038 for n=37). Post-induction endoscopy was carried out in 20 patients. Mayo scores were 0: 1 (5%), 1: 5 (25%), 2: 6 (30%), 3: 8 (40%). Conclusion: Our experience mirrors previously reported, smaller real-world cohorts 1, 2 and demonstrates similar outcomes to those observed in the PURSUIT trials. These data demonstrate a meaningful reduction in clinical and biochemical disease activity as well as a steroid-sparing effect in patients with previously refractory disease. References: . Bosca-Watts MM, et al. Short-term effectiveness of golimumab for ulcerative colitis: Observational multicenter study. World Journal of Gastroenterology. 2016;22(47):10432–10439. . Detrez I, et al. Variability in Golimumab Exposure: A 'Real-Life' Observational Study in Active Ulcerative Colitis. J Crohns Colitis2016; 10 (5): 575–581. Disclosure of Interest: M. Samaan Conflict with: Takeda, Janssen, MSD, Hospira, P Pavlidis: None Declared, A Akintimehi: None Declared, L Medcalf: None Declared, G Chung-Faye: None Declared, P Dubois: None Declared, I Koumoutsos: None Declared, S Anderson: None Declared, J Sanderson: None Declared, BH Hayee: None Declared, P Irving Conflict with: MSD and Takeda, Conflict with: Abbvie, Warner Chilcott, Takeda, MSD, Vifor Pharma, Pharmacosmos, Topivert, Genentech, Hospira and Samsung Bioepis, Conflict with: Abbvie, Warner Chilcott, Ferring, Falk Pharma, Takeda, MSD, Johnson and Johnson, Shire